2018
DOI: 10.3758/s13415-018-0589-1
|View full text |Cite
|
Sign up to set email alerts
|

Community structure analysis of rejection sensitive personality profiles: A common neural response to social evaluative threat?

Abstract: Monitoring social threat is essential for maintaining healthy social relationships, and recent studies suggest a neural alarm system that governs our response to social rejection. Frontal-midline theta (4–8 Hz) oscillatory power might act as a neural correlate of this system by being sensitive to unexpected social rejection. Here, we examined whether frontal-midline theta is modulated by individual differences in personality constructs sensitive to social disconnection. In addition, we examined the sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 64 publications
(122 reference statements)
5
19
0
Order By: Relevance
“…Especially the dACC, a main source of FM-theta, is involved in determining the necessity of eliciting cognitive control by means of a cost-benefit analysis (Shackman et al, 2011;Shenhav, Cohen, & Botvinick, 2016). This corresponds with findings that FM-theta is particularly increased in response to unexpected social rejection feedback (Kortink et al, 2018;van der Molen et al, 2017. Namely, unexpected rejection poses a particularly salient threat to social connectedness due to high amounts of cognitive conflict, uncertainty about what caused the rejection, and negative emotional force.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…Especially the dACC, a main source of FM-theta, is involved in determining the necessity of eliciting cognitive control by means of a cost-benefit analysis (Shackman et al, 2011;Shenhav, Cohen, & Botvinick, 2016). This corresponds with findings that FM-theta is particularly increased in response to unexpected social rejection feedback (Kortink et al, 2018;van der Molen et al, 2017. Namely, unexpected rejection poses a particularly salient threat to social connectedness due to high amounts of cognitive conflict, uncertainty about what caused the rejection, and negative emotional force.…”
supporting
confidence: 76%
“…The aim of our study is to test whether baseline HRV is related to the neural activity evoked by the processing of social evaluative threat. Specifically, our previous studies have shown that processing of unexpected social rejection feedback is associated with a pronounced increase in EEG frontal midline (FM) theta (4 -8 Hz) oscillations (Kortink et al, 2018;van der Molen et al, 2017. The neural sources of this EEG response comprised the dorsal medial PFC, the supplementary motor area, and the dACC.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Other work shows that rejection events in Cyberball also elicit increases in power in the alpha and beta bandwidths, but it is only the increases in frontal midline theta power which tracks individual differences in participant distress (van Noordt et al, 2015). These findings converge with results from alternative paradigms inducing social rejection, which have demonstrated increases in frontal midline theta power time-locked to peer rejection events (Kortink et al, 2018;Morales et al, 2019;van der Molen et al, 2017).…”
Section: Introductionsupporting
confidence: 61%